LINGUISTIC ASPECTS OF THE TRANSLATION OF NATIONAL CULTURAL VOCABULARY - Tukhtakhodjaeva Z.T (Western European Studies, 2024)
This article is devoted to the study of linguistic aspects of the translation of national cultural vocabulary. The cultural concept is recognized as the main unit of linguoculturology, and many authors indicate non-equivalent vocabulary (culture-specific vocabulary), various realities and background knowledge, i.e. meaningful characteristics of specific and abstract names that require additional information about the culture, history and way of life of the people speaking this language for an adequate understanding.
Keywords: linguocultology; cognitive approach; non-equivalent vocabulary